Future stroke risk in the chronic phase of post-percutaneous coronary intervention. - Shinsuke Muraoka (Public Library of Science (PLoS), 2021)
A percutaneous coronary intervention (PCI) is widely performed for acute coronary syndromes or chronic coronary syndromes. Periprocedural stroke is a clinically significant complication during PCI. The incidence of cerebrovascular events (CVEs) after PCI in the chronic phase is obscure. This study aimed to investigate the prevalence of CVEs after PCI in the chronic phase and evaluate the usefulness of a simple coronary artery calcification (CAC) evaluation method. This prospective observational study included 179 patients who underwent PCI between January 2016 and December 2018. The incidence of cerebral infarction was examined from one month after PCI to December 2019. In total, 171 individuals (134 men; mean age, 69.8 ± 9.8 years) were recruited. During a median follow-up period of 33 months, the onset of cerebral infarction was observed in 20 individuals (11.7%). More CAC sites (p = 0.009) and post-PCI for the chronic coronary syndrome (p = 0.049) showed a significant association with future CVEs. There was no significant cervical internal carotid artery stenosis for patients who occurred CVEs. The cutoff value for the number of CAC sites for predicting future CVEs was 4.5. The new and easy method accurately reflected future CVEs risk and may be clinically applicable.